The Effect of Active Mathematics on the Statistical Literacy Skills of Children Aged 5–6 Years at TK Tri Insani Permata Pekanbaru - Anggraini, Ana Lutfia; Solfiah, Yeni; Kurnia, Rita (Journal of English Language and Education, 2025)
Early childhood is a golden period of development, making it essential to introduce statistical concepts in an active and meaningful way. However, statistics instruction in kindergartens tends to be passive and misaligned with children's developmental characteristics. This study employed a quantitative approach using a quasi-experimental one-group pretest-posttest design involving children aged 5–6 years at TK Tri Insani Permata Pekanbaru. Observations were conducted before and after treatment without a control group. The average score increased from 35.67% (pretest) to 78.00% (posttest). Prior to treatment, 93.33% of children were in the "Emerging" category and 6.67% in the "Not Yet Developed" category; after treatment, 53.33% reached the "Very Well Developed" category and 46.67% the "As Expected" category. The effect of Active Mathematics on improving statistical abilities reached 65.80%, with a moderate normalized gain category. Active Mathematics is effective in enhancing early childhood statistical recognition through active, exploratory, and enjoyable learning activities.